Clinical-anatomical basis of methods of stopping blood in tongue injuries, opening and drainage of phlegmons of the floor of the mouth - Eshilov Elbek, Gadayev Asliddin (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
Methods of stopping blood in tongue injuries and opening and drainage of phlegmons of the floor of the mouth involve understanding the relevant anatomy and employing appropriate techniques.